Comparison of different aspects of BMI history to identify undiagnosed diabetes in Japanese men and women: Toranomon Hospital Health Management Center Study 12 (TOPICS 12). Issue 11 (14th May 2014) - Yoshizawa, S.; Heianza, Y.; Arase, Y.; Saito, K.; Hsieh, S. D.; Tsuji, H.; Hanyu, O.; Suzuki, A.; Tanaka, S.; Kodama, S.; Shimano, H.; Hara, S.; et al.
Abstract Aims To examine current BMI and various aspects of BMI history as pre‐screening tools for undiagnosed diabetes in Japanese individuals. Methods This cross‐sectional study included 16 226 men and 7026 women aged 30–75 years without a self‐reported history of clinician‐diagnosed diabetes. We estimated the probability of having undiagnosed diabetes (fasting glucose ≥ 7.0 mmol/l and/or HbA1c ≥ 48 mmol⁄mol (≥ 6.5%) for the following variables: current BMI, BMI in the early 20s (BMI20y), lifetime maximum BMI (BMImax), change between BMI in the early 20s and current BMI (ΔBMI20y−cur), change between BMI in the early 20s and maximum BMI (ΔBMI20y−max), and change between lifetime maximum and current BMI (ΔBMImax−cur). Results The prevalence of undiagnosed diabetes was 3.3% (771/23252) among participants. BMImax, ΔBMI20y–max and current BMI (1‐sd increments) were more strongly associated with diabetes than the other factors (multivariate odds ratio 1.58 [95% CI 1.47–1.70] in men and 1.65 [95% CI 1.43–1.90] in women for BMImax; multivariate odds ratio 1.47 [95% CI 1.37–1.58] in men and 1.61 [95% CI 1.41–1.84] in women for ΔBMI20y–max; multivariate odds ratio 1.47 [95% CI 1.36–1.58] in men and 1.63 [95% CI 1.40‐1.89] in women for current BMI). The probability of having diabetes was markedly higher in those with both the highest tertile of BMImax and greatest ΔBMI20y‐max; however, a substantially lower likelihood of diabetes was observed among individuals with the lowest and middle tertiles of current BMI (< 24.62 kg/m2 in men and < 22.54 kg/m2 in women). Conclusions Lifetime maximum BMI and BMI changes from early adulthood were strongly associated with undiagnosed diabetes. Adding BMI history to people's current BMI would improve the identification of individuals with a markedly higher probability of having undiagnosed diabetes.